Four new species of the subgenus Homoneura from Yintiaoling Nature Reserve, China (Diptera: Lauxaniidae: Homoneura) - You, Pengyan; Chen, Xulong; Li, Wenliang (Zootaxa, 2023)
The subgenus Homoneura Malloch, 1927 is the most diverse in China, with more than 220 known species. Four new species of Homoneura (Homoneura) henanensis group, that is, Homoneura (Homoneura) apiconcava sp. nov., H. (H.) chongqingensis sp. nov., H. (H.) wuxica sp. nov., and H. (H.) yintiaolingica sp. nov., were described from Yintiaoling Nature Reserve, Chongqing, China. A key to the known species of this species group is presented.